LncRNA TUG1 promotes the migration and invasion in type I endometrial carcinoma cells by regulating E-N cadherin switch - Qin Chen; Christoph Schatz; Yixuan Cen; Xiaojing Chen; Johannes Haybaeck; Baohua Li (Elsevier, 2022)
Objective: Accumulating evidence has demonstrated that lncRNA Taurine-upregulated gene 1 (TUG1) plays an important role in regulation of cell morphology, migration, proliferation and apoptosis. Our aim was to evaluate the oncogenic role of TUG1 in type I Endometrial Carcinoma (EC) and explore the precise mechanism of TUG1 involved in tumor progression. Materials and methods: The GSE17025 data set was used to analyze the correlation of TUG1 expression with type I EC patients' prognosis. Furthermore, TUG1 expression profiles were measured by qRT-PCR from carcinoma tissues and adjacent nonneoplastic tissues (NNT) of 105 type I EC patients. The regulation of epithelial-mesenchymal transition (EMT) related molecules, p-AKT and AKT by TUG1 knockdown was investigated using Western blot analysis; meanwhile, the oncogenic roles of TUG1 were evaluated using cell viability and transwell migration/invasion assay in Hec-1-A and Ishikawa cell lines. Results: Firstly, we observed a significant association between higher TUG1 expression and lower survival rate in type I EC patients using the GSE17025 data set. A significant elevation of TUG1 levels was confirmed in type I EC tissues compared with NNT in the 105 type I EC patients, and high expression of TUG1 was associated with lymph vascular space invasion (LVSI) and lymph node metastasis (LNM). Subsequently, TUG1 knockdown could remarkably inhibit the Hec-1-A and Ishikawa cell invasion and migration in the functional experiment. Furthermore, our results showed that the protein levels of E-cadherin increased and N-cadherin decreased significantly, while β-catenin and Vimentin were not significantly altered upon TUG1 silencing in both Hec-1-A and Ishikawa cells. Finally, we found the p-AKT and AKT protein levels, and the rate of p-AKT/t-AKT has a tendency to be down-regulate in Hec-1-A cells, while the AKT pathway was not change significantly in Ishikawa cells after TUG1 knockdown. Conclusion: Collectively, our data reveal that TUG1 might be regarded as an oncogenic molecule that promotes type I EC cells metastasis leading to tumor progression, at least partially, by regulating E-N cadherin switch and the AKT pathway.